UMP launched AsarFonts - enriching Jawi writing using technology - UMP, PNC

(untitled)
Research conducted by Ustaz Asar from Centre for Modern Languages & Human Sciences (CMLHS), Universiti Malaysia Pahang (UMP) produced a Jawi writing software called AsarFonts.